Innovative Approaches to Teaching Technical Communication - Bridgeford, Tracy; Kitalong, Karla Saari; Selfe, Dickie (University Press of Colorado, 2004)
Programs in technical writing, technical communication, and/or professional communication have recently grown in enrollment as the demand among employers for formally prepared technical writers and editors has grown. In response, scholarly treatments of the subject and the teaching of technical writing are also burgeoning, and the body of research and theory being published in this field is many times larger and more accessible than it was even a decade ago. Although many theoretical and disciplinary perspectives can potentially inform technical communication teaching, administration, and curriculum development, the actual influences on the field's canonical texts have traditionally come from a rather limited range of disciplines. Innovative Approaches to Teaching Technical Communication brings together a wide range of scholars/teachers to expand the existing canon.